Sports Science Research and Technology Support International Congress, icSPORTS 2013, Vilamoura, Algarve, Portugal, September 20-22, 2013. Revised Selected Papers - Cabri, Jan; Pezarat Correia, Pedro; Barreiros, João (Communications in Computer and Information Science, 2015)
This book constitutes the thoroughly refereed proceedings of the First International Congress on Sports Science Research and Technology Support, icSPORTS 2013, Held in Vilamoura, Algarve, Portugal, in September 2013. The 7 full papers were carefully reviewed and selected from 90 submissions. The papers highlight the benefits of kinds of technologies for sports, either in general, or regarding particular cases of application.